2008
DOI: 10.1002/ana.21292
|View full text |Cite
|
Sign up to set email alerts
|

Clade‐specific differences in neurotoxicity of human immunodeficiency virus‐1 B and C Tat of human neurons: significance of dicysteine C30C31 motif

Abstract: This study provides important insights into differential neurotoxic properties of B- and C-Tat, and offers a basis for distinct differences in degree of HIV-1-associated neurological deficits observed in patients in India. Additional studies with patient samples are necessary to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(143 citation statements)
references
References 46 publications
8
133
0
Order By: Relevance
“…This was further confirmed by site specific mutagenesis in which we mutated the Cys31 in clade B Tat to a Ser and mutated Ser31 to Cys in clade C Tat and then compared their neurotoxic potential. This is consistent with a recent study that implicated the role of Cys31 in Tat-mediated neurotoxicity in primary neurons (Mishra et al, 2008). Interestingly, however, both clade B and C Tat could similarly immunoprecipitate the NMDA receptor.…”
Section: Discussionsupporting
confidence: 92%
“…This was further confirmed by site specific mutagenesis in which we mutated the Cys31 in clade B Tat to a Ser and mutated Ser31 to Cys in clade C Tat and then compared their neurotoxic potential. This is consistent with a recent study that implicated the role of Cys31 in Tat-mediated neurotoxicity in primary neurons (Mishra et al, 2008). Interestingly, however, both clade B and C Tat could similarly immunoprecipitate the NMDA receptor.…”
Section: Discussionsupporting
confidence: 92%
“…These primary neurons express tyrosine hydroxylase and most of the Tuj1 positive neurons also express tyrosine hydroxylase (supplemental Fig. 1 A, available at www.jneurosci.org as supplemental material) indicating the predominant dopaminergic phenotype of these cells (Mishra et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Human CNS progenitor cell cultures were prepared from 8-to 12-week-old embryos obtained from elective medical termination of first trimester pregnancies performed at the local hospital after informed consent as per the approved protocol of the institutional human ethics committee in compliance with the recommendations of the Indian Council of Medical Research, Government of India. Primary cultures of human CNS progenitor cells were prepared and cultured as monolayers on poly-Dlysine coated chamber slides in serum-free neurobasal medium and neurons were derived from them as described previously (Mishra et al, 2008). Neuronal differentiation involved changing the growth factors in the progenitor media to brain-derived neurotrophic factor (BDNF, 10 ng/ml) and platelet-derived growth factor (PDGF)-A/B (10 ng/ml) for 3 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…41 It has been found that tat expression differs between HIV clades, and further proposed that a defect in the dicysteine motif in tat in clade C leads to lower levels of neurotoxicity. 42 The implications are that in regions where clade C is predominant, such as South Africa, lower rates of HAND might be expected. Recent work in India, where clade C is also predominant has not supported this idea.…”
Section: Mechanisms Of Neuro-degenerationmentioning
confidence: 99%
“…[23][24][25] Variability has been attributed to differences in the dicysteine motif within the neurotoxic region of B-Tat, producing a greater degree of Tat-induced apoptosis. 26,27 However, other viral proteins, such as gp120, may be as neurotoxic. The clade sequence, levels of proviral DNA and tat protein, together with their impact on neuropsychological functions and neuro-imaging findings, is the subject of a study currently being conducted by our group.…”
Section: Introductionmentioning
confidence: 99%